Need of Quality in Basic Education: A Study of Uttar Pradesh. - Tyagi, R.C. and Siddiqui, Tarannum (2012)
The National Policy on Education, as revised in 1992, had emphasized the need for a substantial improvement in thequality of education to achieve essential levels of learning. The Programme of Action, 1992, stressed the need to lay down Minimum Levels of Learning (MLL) at primary and upper primary stage. This need emerged from the basic concern that irrespective of caste, creed, location or sex, all children must be given access to education of comparable standards. The MLL strategy for improving the quality of elementary education was seen as an attempt to combine quality with equity. A strong focus on quality issues in elementary education underpins all efforts under SSA, which has increasingly become centre point, as the programme advances. The quality issue in elementary education revolves around the quality of infrastructure and support services, opportunity time, teacher characteristics and teacher motivation, pre-service and in-service education of teachers, curriculum and teaching-learning materials, classroom processes, pupil evaluation monitoring and supervision.